Seismic Analysis of Double Unit Tunnel Form Building Subjected to Out-of-Plane Lateral Cyclic Loading - Shamilah Anuar; Afifuddin Azizuddin (Salehan Institute of Higher Education, 2022)
Most of the high-rise buildings for commercial and residential purposes in Malaysia are constructed using a tunnel formwork system. This type of building becomes a favor due to the fast construction and cost-effectiveness. However, the research on the behavior of Tunnel Form Building (TFB) under the seismic effect is still insufficient and requires further investigation. Therefore, the safety level of double unit TFB subjected to weak plane (out-of-plane) was investigated in this study. The TFB was designed using a non-seismic provision to represent an existing condominium building constructed in Selangor. Ten past earthquake records categorized as major, moderate, and low magnitudes were utilized. The behavior of the double unit TFB was analyzed using the Ruaumoko 2D program. The ultimate lateral load, displacement, pseudo-spectral acceleration (PSA), pseudo-spectral displacement (PSD), and mode shape of TFB were also analyzed. Based on the findings, most of the selected earthquake records exceeded the lateral capacity of TFB. The building experienced a major damage under 6.9 Richter scale of Imperial Valley, 7.3 Richter scale of San Joaquin Valley, and 7.9 Richter scale of Denali Earthquakes excitations. Therefore, these findings suggested if any similar magnitudes of unpredicted seismic events would occur in the future, significant damages may be experienced by the existing TFB in Malaysia. Doi: 10.28991/CEJ-2022-08-11-012 Full Text: PDF